2021
DOI: 10.3390/sym13020196
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric Modeling of Diversification Strategy and Organizational Structure on Financial Performance: Evidence from China

Abstract: Diversification is a strategy adopted by many enterprises in the process of expansion. The success of the diversification of an enterprise mainly depends on the choice and implement of strategy; choosing an organizational structure that fits the type of diversification strategy used is fundamental to improving financial performance. Based on the empirical research method, this study establishes a symmetric model of diversification strategy and organizational structure on financial performance and selects data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…According to the Synergy Effects theory, enterprises implementing diversification strategies tend to be more willing to share resources and diffuse capabilities [23], which has an important effect on resource allocation and synergy among the industries they are involved in promotion, which makes the cross-industry convergence of enterprise technology, resources, and talents more rapid. Simultaneously, diversification is the business strategy adopted by firms, and its successful execution necessitates the synergy effect of many management elements [24]. As a new kind of cross-border cooperation among firms, industrial convergence adds value by leveraging the complementary characteristics of many industries.…”
Section: The Mediating Role Of Diversification Strategymentioning
confidence: 99%
“…According to the Synergy Effects theory, enterprises implementing diversification strategies tend to be more willing to share resources and diffuse capabilities [23], which has an important effect on resource allocation and synergy among the industries they are involved in promotion, which makes the cross-industry convergence of enterprise technology, resources, and talents more rapid. Simultaneously, diversification is the business strategy adopted by firms, and its successful execution necessitates the synergy effect of many management elements [24]. As a new kind of cross-border cooperation among firms, industrial convergence adds value by leveraging the complementary characteristics of many industries.…”
Section: The Mediating Role Of Diversification Strategymentioning
confidence: 99%
“…Foreign assets to total Global assets: Foreign assets to total global assets are one of the properties selected for the measurement of the possible implications of internationalization. Cao et al (2021) posited that foreign assets lagged with the banks' global total assets giving a proportional percentage of foreign branches' performance. According to Brahmana et al (2018), foreign assets to total global assets are closely associated with the internationalization of banking performance, De Massis et al ( 2018) revealed that foreign assets to total global assets had a positive effect on the financial performance and value creation in meeting corporate set goals and objectives.…”
Section: Internationalizationmentioning
confidence: 99%
“…Different studies have looked at strategic decisions from different perspectives, which can be mainly classified into three categories as follow. The first is the content of a strategic decision covering topics such as diversification strategy, concentration strategy, cost leadership and product differentiation strategies (O'Brien et al 2014, Banker et al 2014, Cao et al 2021). The second is the strategic decision-making process, which explores how strategic decisions are made and what factors affect them (Menda and Dilts 1997, De Wit and Meyer 2010, Merendino et al 2018, Chin et al 2021).…”
Section: Strategic Management Strategy and Diversification As The Con...mentioning
confidence: 99%